Muzakkii Happiness in Compliance to Pay Zakat Among Lecturers and Educators - Wahyu, Agung Minto; Chusniyah, Tutut; Harsono, Yudi Tri; Zahra, Gebi Angelina; Setiyowati, Ninik (KARSA Journal of Social and Islamic Culture, 2022)
Humans are social creatures who need the help of others. The behavior of support is known as prosocial behavior. One form of prosocial behavior for Muslims is to pay zakat. Some studies show that people who dutifully pay zakat can bring happiness. This study aims to examine the effect of compliance with zakat on happiness. The sample of this study amounted to 270 people using the purposive sampling technique with the criteria, namely 1) the lecturers and educational personnel; 2) Muslim; 3) have an income of overall Rp 5.585.400/month after being reduced to basic needs. Data collection was done using a compliance scale to pay zakat, which the researcher developed based on Blass's[1] theory and the oxford happiness questionnaire developed by Hills and Argyle[2]. The results of hypothesis testing show that compliance with zakat significantly affects the happiness of the muzakkii from among the lecturers and educational personnel to the value of R = 0,326 and the value of RTwo = 0,106. The Value of RTwo shows that compliance with zakat determines happiness by 10.6%, while other variables cause 89.4%. The implications of this research for muzakkii are 1) do not make the zakat a burdensome deed; 2) pay zakat directly; 3) interact with the zakat receiver. For further research, 1) expand the scope of the respondents; 2) use other relevant respondents; 3) investigate the role of the independent variable of another.